Neck telangiectasia: A case with a twist - Florica Sandru (Romanian Medical Journal, 2020)
Telangiectasia represents a sign on the skin underlining multiple conditions, characterised by red/purple/blue thin lines caused by dilatation of capillaries/arterioles/venules. Similar lesions may be detected during a surgical procedure at the surface of a solid organ. Pathological conditions associating the lesion are: dermatomyositis, scleroderma, lupus and the syndromes of ataxia-telangiectasia, respective hereditary hemorrhagic telangiectasia. We introduce a male case with anterior and lateral cervical enlargement with local skin changes of telangiectasia type. We introduce a male case with anterior and lateral cervical enlargement with local skin changes of telangiectasia type. The twist of the case is that, despite neck tegument red thin lines, the subject actually had a severe form of thyroid cancer. This is a case presentation. This is an 82-year old non-smoker male from non-endemic area admitted for rapidly enlargement of a tumor mass at neck in addition with local skin changes like telangiectasia and erythema as well as speech, eating and breathing intermittent disturbances. Thyroid function was normal. Thyroid ultrasound showed an enlargement of right lobe, of 3.7 by 4 by 7 cm (centimeter), mostly displayed by a macronodule with mix structure, of oval shape, with extension to isthmus, which is well shaped, of 5.7 by 4 by 5.2 cm. The data are highly suggestive for a thyroid cancer, thus the patient was further referred for total thyroidectomy. The changes of neck skin like telangiectasia and redness may exceptionally be caused by an aggressive thyroid cancer.